Religious Commitment and Body Appreciation: Exploring the Mediating Role of Positive Orientation and Gratitude in a Polish Sample - Razmus, Magdalena (Journal for the scientific study of religion, 2024)
Although religiosity has been recognized as a predictor of health and well-being, links between religiosity and body image have not been extensively examined. The objective of our study was to explore possible pathways through which religious commitment might be associated with body appreciation in a Polish sample. Participants (N = 262) completed measures of religious commitment, positive orientation, gratitude, and body appreciation. Results demonstrated that religious commitment was positively related to body appreciation. Moreover, both positive orientation and gratitude mediated this relationship. A higher level of religious commitment was associated with a higher level of positive orientation and gratitude that, in turn, was related to a greater body appreciation. We concluded that religious commitment may be related to people's loving and respectful relationship with their bodies.